A stereoselective approach to bioactive secolignans: Synthesis of peperomin C and its analogues - Darunee Soorukram (2018)
© 2014 Elsevier Ltd. All rights reserved. A stereoselective approach to secolignans is described. The key synthetic strategy involves an asymmetric aldol reaction to control the creation of the stereogenic center at the β-carbon of the target secolignans. In the present work, peperomin C and its analogues, i.e., 2,6-didehydropeperomin C and 2-epi-peperomin C were successfully synthesized in good yields with high stereoselectivities.